2022
DOI: 10.3389/fmedt.2022.1053719
|View full text |Cite
|
Sign up to set email alerts
|

Valuing infertility treatment: Why QALYs are inadequate, and an alternative approach to cost-effectiveness thresholds

Abstract: KEYWORDSinfertility treatment, quality-adjusted life-year (QALY), cost-benefit analysis (CBA), discrete choice experiment (DCE), willingness-to-pay (WTP), health technology assessment (HTA), value of a statistical baby (VSB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…Traditional health technology assessment (HTA) outcome metrics, which focus on health-related quality of life, such as cost per quality-adjusted life-years (QALYs) or disability-adjusted lifeyears (DALYs), are debatably inadequate when used for fertility treatments (21,29,30). Quality-adjusted life-years and DALYs were designed for, and thus are best suited to, measuring changes in health-related quality of life for already existing lives with utility weights derived from societal preferences for different health states (31).…”
Section: Inadequacy Of Traditional Health Technology Assessment Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditional health technology assessment (HTA) outcome metrics, which focus on health-related quality of life, such as cost per quality-adjusted life-years (QALYs) or disability-adjusted lifeyears (DALYs), are debatably inadequate when used for fertility treatments (21,29,30). Quality-adjusted life-years and DALYs were designed for, and thus are best suited to, measuring changes in health-related quality of life for already existing lives with utility weights derived from societal preferences for different health states (31).…”
Section: Inadequacy Of Traditional Health Technology Assessment Methodsmentioning
confidence: 99%
“…This only captures a component of the utility/disutility associated with fertility treatment, much of which is associated with non-health outcomes reflecting achieving life goals. Essentially, by undergoing fertility treatment individuals are buying hope to have a child and the potential to create a meaningful life, rather than improving health or avoiding disease (21,30,32,33). The challenges of using QALYs to value fertility treatment are highlighted by a review of cost-effectiveness analyses for fertility treatments (34) that showed that only one of 14 studies employed QALYs.…”
Section: Inadequacy Of Traditional Health Technology Assessment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used standard HTA handbooks, guidelines, and articles 13,5459 to determine the dominant view regarding which costs and outcomes are relevant to consider for each study objective (see Figure 1). Green checkmarks indicate which costs and outcomes should be included, while red crosses indicate those that should be excluded.…”
Section: Methodsmentioning
confidence: 99%